Effect of Baduanjin exercise in a blended online-offline model on cognitive function and peripheral blood BDNF levels in older adults - Zhihui Zhou; Jiawei Wang; Fanhui Kong; Qianqian Zhang (Frontiers in Physiology)
ObjectiveThis study aimed to examine the effect of 12-week Baduanjin exercise on cognitive function and peripheral blood brain-derived neurotrophic factor (BDNF) levels in the older adults, utilizing a blended online and offline model.MethodsA total of 40 older adults with low physical activity levels were randomly assigned to either Baduanjin group (BG, n = 20, age: 63.75 ± 1.41 years) or control group (CG, n = 20, age: 63.10 ± 1.65 years). The BG participated in 12-week Baduanjin exercise, conducted 3 times per week, integrating both online and offline components. Each session comprised a 60-min structure, including a 10-min warm-up, 40 min of Baduanjin exercise, and a 10-min cool-down period. Cognitive function and peripheral blood BDNF levels were assessed prior to and following the 12-week intervention.Results(1) After 12-week intervention, BG exhibited significant improvements in MoCA (P < 0.01), and MoCA of BG was significantly higher than CG (P < 0.05). (2) After 12-week intervention, BG exhibited significant improvements in DST-F (P < 0.05), DST-B (P < 0.05), VFT (P < 0.01), Stroop-A (P < 0.05), and Stroop-RT (P < 0.05). DST-F, DST-B, VFT, and Stroop-A scores of BG were significantly higher than those of the CG (P < 0.05) after intervention. And Stroop-RT was significantly lower than CG (P<0.05) after intervention. (3) BDNF levels: After 12-week intervention, BG exhibited significant improvements in BDNF (P < 0.01), and BDNF of BG was significantly higher than CG (P < 0.05). (4) A significant positive linear correlation was identified between MoCA scores and BDNF levels (r = 0.488).Conclusion12-week Baduanjin intervention in a blended online-offline model can significantly improve cognitive function in the older adults. The improvement in cognitive levels induced by exercise is accompanied by an increase in peripheral blood BDNF content, and there is a significant positive correlation between the two factors.